Antioxidant Activity from synthesis product of Hydoxycinamic Acid Derivative.: Antioxidant Activity from synthesis product of Hydoxycinamic Acid Derivative. - Novia, Ni Kadek Ayu (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2021)
Hydroxycinamic acid derivatives have potential as antioxidants. The synthesis of hydroxycinamic acid derivatives from p-coumaric acid with hexylamine yielded 4-(3-hexylamine-3-oxopropenyl) phenyl acetate compounds. Synthesis is carried out through the acetylation, chlorination, and amidation reaction stages. Amidation products were characterized by TLC test, melting point determination, FT-IR spectroscopy. The antioxidant activity was tested using 1,1-diphenyl picrylhydrazyl (DPPH). The results showed that the compound obtained was a white crystalline solid (yield 15.59%, melting point 104 - 106 °C). Compound 4 only shows very weak antioxidant activity with an IC50 value of 11453.03 μg / mL%. Thus compound 4 has no potential as an antioxidant.